A Case Series on Ultra Sound Guided Peng Block for Postoperative Analgesia in Patients Undergoing Proximal Femur Nailing - Dr M Suchitra; Dr. Vineet Reddy G; Dr.Asha latha; Dr.Subhashree J, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Hip fracture is most common major injury in the elderly and important cause of mortality and morbidity. Pain free rehabilitation followed by early mobilization are required for clinical and functional recovery after proximal femur fracture. PEricapsular Nerve Group (PENG)should always be conducted in addition to spinal or general anesthesia to prolong postop analgesia. PENG block appears to be less invasive more effective compared to other methods. Materials &Methods: we conducted a case series of 20 cases of age group 50-75 undergoing elective surgery posted for PFN.they were given ultrasound guided PENG blockwith 20 ml of 0.25% bupivacaine for post op analgesia. Results Pain intensity was measured using NRS score every 2nd hour for upto 12 hours postoperatively. Most of the patients reported NRS score of 2-3 up to 8 hours representing mild pain and NRS score of 4 representing moderate pain in the next 4 hours. Conclusion: PENG block provides good postop analgesia in the first 12 hrs of immediate postop period in patients underwent PFN.